Duplicate checking Strategies for Selecting Topics for Graduation Thesis Based on Maximum Public Sequence. Issue 3 (May 2019) - Yu, Guorui; Huang, Li; Sun, Jiewen; Liao, Shangchun
Abstract: The system is based on the undergraduate thesis management system as the practice platform, focusing on the realization of the thesis topic check function. The current check-up detection system is based on the entire contents of the query, and does not meet the requirements for an undergraduate thesis query. According to the characteristics of the thesis, the system first divides the keywords into the topic, selects the irrelevant parts, then removes the irrelevant words, and finally checks the keywords in the topic, and realizes the efficient and accurate check for inspection.